Immune infiltration profiling in gastric cancer and their clinical implications. Issue 9 (26th July 2021) - Ren, Feifei; Zhao, Qitai; Zhao, Minghai; Zhu, Shaogong; Liu, Bin; Bukhari, Ihtisham; Zhang, Kai; Wu, Wanqing; Fu, Yuming; Yu, Yong; Tang, Youcai; zheng, Pengyuan; et al.
Abstract: The abundance and type of immune cells in the tumor microenvironment (TME) significantly influence immunotherapy and tumor progression. However, the role of immune cells in the TME of gastric cancer (GC) is poorly understood. We studied the correlations, proportion, and infiltration of immune and stromal cells in GC tumors. Data analyses showed a significant association of infiltration levels of specific immune cells with the pathological characteristics and clinical outcomes of GC. Furthermore, based on the difference in infiltration levels of immune and stromal cells, GC patients were divided into two categories, those with "immunologically hot" (hot) tumors and those with "immunologically cold" (cold) tumors. The assay for transposase‐accessible chromatin using sequencing and RNA sequencing analyses revealed that the hot and cold tumors had altered epigenomic and transcriptional profiles. Claudin‐3 (CLDN3) was found to have high expression in the cold tumors and negatively correlated with CD8 + T cells in GC. Overexpression of CLDN3 in GC cells inhibited the expression of MHC‐I and CXCL9. Finally, the differentially expressed genes between hot and cold tumors were utilized to generate a prognostic model, which predicted the overall survival of GC as well as patients with immunotherapy. Overall, we undertook a comprehensive analysis of the immune cell infiltration pattern in GC and provided an accurate model for predicting the prognosis of GC patients. Abstract : Immune hot and cold tumors showed the difference in epigenetic and transcriptomic alterations. Claudin 3 (CLDN3) was negatively correlated with the infiltration of CD8 + T cells. Overexpression of CLDN3 in gastric cancer (GC) cells inhibited the expression of MHC‐I and CXCL9. The prediction model performed well in predicting overall survival of patients with GC and patients with immunotherapy treatment.